The Agronomic Potential of the Invasive Brown Seaweed Rugulopteryx okamurae: Optimisation of Alginate, Mannitol, and Phlorotannin Extraction - Miguel A. Rincón-Cervera; Irene de Burgos-Navarro; Tarik Chileh-Chelh; El-Hassan Belarbi; Miriam Álvarez-Corral; Minerva Carmona-Fernández; Mohamed Ezzaitouni; José L. Guil-Guerrero (Plants)
Rugulopteryx okamurae is an invasive brown macroalga that has recently proliferated in the western Mediterranean Sea, causing significant environmental challenges. This alga, however, contains valuable bioactive compounds—alginate, mannitol, and phlorotannins—that can serve as biofertilizers to promote plant growth and aid in bioremediation of degraded or contaminated soils. This study focused on optimizing the extraction of these compounds from R. okamurae, transforming an ecological issue into a beneficial resource. Algae samples collected from the Spanish Mediterranean coast were processed through a randomized factorial response surface design. Extraction conditions varied by time, temperature, algae-to-solvent ratio, and ethanol-to-water ratio to determine optimal yields. The highest yields achieved were 29.4, 11.9, and 0.35 g/100 g for alginate, mannitol, and phlorotannin’s under extraction conditions of 6, 6, and 3 h; 58.8, 60.0, and 60.0 °C; and an algae:solvent ratio of 1:50, 2:45, and 1.40 g/mL, respectively. Characterization of the extracted sodium alginate using 1H-NMR, FTIR, and high-resolution electron microscopy confirmed its high purity and typical morphological features. This study highlights a sustainable approach to mitigating the invasive spread of R. okamurae while supporting soil health and sustainable agriculture. Harnessing this invasive species’ biofertilizer potential provides a dual solution, aiding marine ecosystem conservation and developing eco-friendly agricultural practices.